Peningkatan Keterampilan Berbahasa Indonesia melalui Pelatihan Media Digital untuk Siswa SD, SMP, dan SMA di Kampung Kweel - Hanova Rani Eka Retnaningtyas; Ekfindar Diliana; Dina Mariana Br. Tarigan (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Indonesian language skills are fundamental competencies that support students’ learning processes and communication; however, the use of digital media in learning remains limited, particularly in remote areas such as Kampung Kweel. This community service program aims to improve the Indonesian language skills of elementary, junior high, and senior high school students through digital media training using a participatory approach, including preparation, socialization, training, mentoring, and evaluation. The activities involve both theoretical instruction and practical exercises, such as reading digital texts, writing using applications, and creating simple videos to enhance speaking skills. The results show improvements in students’ reading, writing, speaking, and listening skills, as indicated by pre-test and post-test scores, while questionnaire results reveal positive responses toward digital media use. Thus, digital media training is effective in improving language skills as well as students’ motivation and confidence in learning.